2013
DOI: 10.1590/s0080-623420130000600014
|View full text |Cite
|
Sign up to set email alerts
|

Perfil dos idosos que cochilam

Abstract: RESUMO ABSTRACTThis study aimed to characterize the elderly who naps according to sociodemographic characteristics and frailty. A descriptive, cross-sectional study part of the multicenter project Frailty in the Elderly Brazilians. We evaluated 1,866 elderly people using a sociodemographic questionnaire. The frailty was assessed using the phenotype proposed by Fried. The data were analyzed with descriptive statistics. The results showed that the profile of the elderly who naps consists predominantly of women, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
0
1
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 26 publications
0
0
1
8
Order By: Relevance
“…The average reported length of a nap in our study (mean age: 61, mean nap duration: 52 min) was longer than in other healthy adult populations (mean age: 53.8 respectively 59.9; mean nap duration: 19.8 min respectively 34.6 min) [4,5]. However, the average length of a nap in our study was comparable to elderly populations napping on average 54 min and 55 min (mean age 73 and 77) [22,23]. We found that during the night preceding a nap, sleep duration was shorter, and sleep quality was lower.…”
Section: Prevalence Of Napperscontrasting
confidence: 55%
“…The average reported length of a nap in our study (mean age: 61, mean nap duration: 52 min) was longer than in other healthy adult populations (mean age: 53.8 respectively 59.9; mean nap duration: 19.8 min respectively 34.6 min) [4,5]. However, the average length of a nap in our study was comparable to elderly populations napping on average 54 min and 55 min (mean age 73 and 77) [22,23]. We found that during the night preceding a nap, sleep duration was shorter, and sleep quality was lower.…”
Section: Prevalence Of Napperscontrasting
confidence: 55%
“…A respeito da associação entre a Orientação Temporal e o escore do PSQI, cabe discutir que o ambiente das ILPI, na maioria das vezes, é caracterizado pela inatividade e por rotinas invariáveis, bem como pela escassez de estímulos cognitivos (DOMICIANO et al, 2016;FERNANDES et al, 2016;SILVA et al, 2015;TRINDADE et al, 2013;TABALI et al, 2013;SCORSOLINI -COMIN;SANTOS, 2013), fatores que podem contribuir para a dificuldade na orientação do idoso em relação ao tempo (DOMICIANO et al,2016;DIAS, FERNANDES et al, 2016). Estas questões merecem um aprofundamento das investigações, que foge aos objetivos deste estudo.…”
Section: Discussão Discussãounclassified
“…A associação entre a duração dos cochilos e as variáveis gênero e fragilidade foi verificada em um estudo realizado com dados do projeto multicêntrico Fragilidade em Idosos Brasileiros, no qual foram avaliados 3.075 indivíduos com idade igual ou superior a 65 anos, 61,7% dos quais relataram cochilar durante o dia (SANTOS et al, 2016;SANTOS et al, 2013). No referido estudo observou-se também duração dos cochilos maior entre idosos do gênero masculino e frágeis (SANTOS et al, 2016;SANTOS et al, 2013).…”
Section: Discussão Discussãounclassified
See 2 more Smart Citations